Evans syndrome with severe thrombocytopenia: a rare presentation - Kamalamma, Rugmini; ML, Siddaraju; Badam, Swathi; Mahankali, Niranjan (International Journal of Contemporary Pediatrics, 2016)
Evans syndrome is a rare disease characterized by the sequential or simultaneous presence of autoimmune haemolytic anemia and immune thrombocytopenia with a chronic relapsing and remitting course. Most of them present with severe anemia and moderate thrombocytopenia while neutropenia is associated in some cases. Associated laboratory parameters include unconjugated hyperbilirubinemia, decreased total serum IgG and IgM levels, presence of non-cross reacting auto antibodies against erythrocytes, platelets and in some cases against neutrophils. Management of evans syndrome includes glucocorticosteroids as the first line therapy and IVIG as second line treatment. Resistant cases are treated with cyclosporine, mycophenolate mofetil, vincristine, danazol, rituximab (monoclonal anti-CD20 antibody), alemtuzumab (humanized monoclonal anti-CD52 antibody). Autogenic or allogenic hematopoietic stem cell transplantation (HSCT) is the only curative option available. Here we are presenting an adolescent boy with Evans syndrome who presented with severe thrombocytopenia and moderate degree of haemolytic anemia and responded well to first line oral corticosteroid therapy.